The Detection of Artificially Made Defects in Welded Joint with Ultrasonic Defectoscopy Phased Array - Dopjera, Daniel; Mičian, Miloš (Manufacturing Technology Journal, 2014)
The article describes the fundamental physical principles of the ultrasonic defectoscopy Phased Array, which provides new possibilities in the non-destructive testing (NDT) of materials, especially of welded joints. There is a report from the ultrasonic testing of welded joint with ultrasonic flaw detector OmniScan MX2 from the company Olympus NDT. The artificial defects were designed in software ESBeamTool 5 from the company Eclipse Scientific, which simulates the geometrical ultrasonic beams spread. Then, ultrasonic testing was performed at the same welded joint with artificially made defects. At the end, data from both ultrasonic testing were evaluated. The same procedure will be used for the design of ultrasonic inspection TOFD (Time of Flight Diffraction) and Phased Array at welded joints of gas pipelines.
Keywords: NDT; Phased Array; ESBeamTool 5